Genome re-sequencing of semi-wild soybean reveals a complex Soja population structure and deep introgression. - Jie Qiu (Public Library of Science (PLoS), 2014)
Semi-wild soybean is a unique type of soybean that retains both wild and domesticated characteristics, which provides an important intermediate type for understanding the evolution of the subgenus Soja population in the Glycine genus. In this study, a semi-wild soybean line (Maliaodou) and a wild line (Lanxi 1) collected from the lower Yangtze regions were deeply sequenced while nine other semi-wild lines were sequenced to a 3-fold genome coverage. Sequence analysis revealed that (1) no independent phylogenetic branch covering all 10 semi-wild lines was observed in the Soja phylogenetic tree; (2) besides two distinct subpopulations of wild and cultivated soybean in the Soja population structure, all semi-wild lines were mixed with some wild lines into a subpopulation rather than an independent one or an intermediate transition type of soybean domestication; (3) high heterozygous rates (0.19-0.49) were observed in several semi-wild lines; and (4) over 100 putative selective regions were identified by selective sweep analysis, including those related to the development of seed size. Our results suggested a hybridization origin for the semi-wild soybean, which makes a complex Soja population structure.